Food safety in informal public markets in Kenya: perceptions of stakeholders in the food chain - Kuboka, Maureen; Grace, Delia; Artursson, Karin; Lindahl, Johanna; Carlsson, Gunnar; Mutua, Florence (Frontiers in Sustainable Food Systems, 2024)
Informal markets play a crucial role in providing fresh and nutritious foods for people in low and middle-income countries. However, the safety of food sold in these markets remains a major concern, contributing to a high burden of foodborne illnesses.This study was designed to analyze stakeholder perceptions of food safety in selected informal public markets in Kenya. Eight focus group discussions and 15 key informant interviews were conducted. In addition, two workshops were held to validate the findings.We found that consumers and vendors confounded food quality, especially freshness, with safety, and paid more attention to appearance and physical qualities than food safety. Information (such as branding and expiry dates) and heuristic cues (such as the flow of buyers and the presence of flies) were used to assess food safety. Meat was perceived as the food most likely to cause disease.Chemical hazards in fresh produce and aflatoxins in maize were mentioned as priority hazards by both vendors and consumers. Stakeholders more knowledgeable about food safety considered microbial hazards as a top priority. Although diarrheal diseases were reported to be prevalent in the communities, these were often thought to be the result of agri-chemical residues in fresh produce or the consumption of high-fat foods, and not commonly linked to bacteria in food.Gaps identified during the interviews included poor infrastructure, inadequate food safety knowledge, insufficient or prohibitive policies, insufficient political will, and poor food safetyrelated practices. There were few mentions of lack of motivation or incentives for behavior change, or insufficient consumer demand for food safety.To fill the gaps, several opportunities were discussed, including contextualizing policies and regulations, investing in infrastructure, capacity building, and training, and promoting involvement and collaboration among various stakeholders. This study has highlighted gaps and misperceptions that need to be addressed through proper knowledge and awareness to effectively combat foodborne disease challenges. Behavioral change approaches to improve food safety are recommended.